2001
DOI: 10.1038/35098059
|View full text |Cite
|
Sign up to set email alerts
|

Selective assembly on a surface of supramolecular aggregates with controlled size and shape

Abstract: The realization of molecule-based miniature devices with advanced functions requires the development of new and efficient approaches for combining molecular building blocks into desired functional structures, ideally with these structures supported on suitable substrates 1-4. Supramolecular aggregation occurs spontaneously and can lead to controlled structures if selective and directional non-covalent interactions are exploited. But such selective supramolecular assembly has yielded almost exclusively crystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
749
5
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 832 publications
(795 citation statements)
references
References 19 publications
32
749
5
9
Order By: Relevance
“…Previous studies address that molecules with N≡Cs groups easily form dimers and trimers via weak hydrogen bonds. 28,44,45 On the basis of these literature reports and the present experimental data, the adsorption models of network I and II were tentatively suggested in Figure 5a Structural Transitions and Dynamic Processes. The steady-state STM experiments in an electrochemical environment demonstrated that depending on the substrate charge density, three types of ordered chiral supramolecular adlayers can be observed on a Au(111) surface.…”
Section: Network Patterns (Region II 02 F 065 V)supporting
confidence: 59%
“…Previous studies address that molecules with N≡Cs groups easily form dimers and trimers via weak hydrogen bonds. 28,44,45 On the basis of these literature reports and the present experimental data, the adsorption models of network I and II were tentatively suggested in Figure 5a Structural Transitions and Dynamic Processes. The steady-state STM experiments in an electrochemical environment demonstrated that depending on the substrate charge density, three types of ordered chiral supramolecular adlayers can be observed on a Au(111) surface.…”
Section: Network Patterns (Region II 02 F 065 V)supporting
confidence: 59%
“…[1][2][3] Many of these applications rely on the formation of thin films of ordered structures of porphyrins and related compounds. [4][5][6][7] Intermolecular interactions such as dipole-dipole, 8 hydrogen bonding, 8 and coordination 9 in porphyrin building blocks are being used to create selfassembled structures on surfaces with increasing sophistication. Itaya et al demonstrated that the ordering of porphyrin molecules on metal surfaces can be promoted by a passivating layer of iodine, which reduces the adsorbate-substrate interaction and facilitates surface diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…For these methods no precise positioning of the components is attainable. In order to move from disordered solid samples to organized monolayers, it is necessary to assemble the molecules, via covalent [1,2,3,4] or non-covalent interactions [5][6][7][8][9][10][11][12] on a substrate and to study their properties at this interface. Amongst the responsive molecules, those addressable with light and able to give a strong emission signal are very appealing since any type of surface can be used and no wiring is required for their activation [13,14].…”
Section: Introductionmentioning
confidence: 99%